Book review: Islam Dot Com: contemporary Islamic discourse in cyberspace - Faisal Ashaari (Penerbit Universiti Kebangsaan Malaysia, 2010)
This is the review of the book Islam Dot Com: Contemporary Islamic Discourse in Cyberspace